Self-polarization induced by lattice mismatch and defect dipole alignment in (001) BaTiO3/LaNiO3 polycrystalline film prepared by magnetron sputtering at low temperature. Issue 76 (19th August 2015) - Hou, Y. F.; Zhang, T. D.; Li, W. L.; Cao, W. P.; Yu, Y.; Xu, D.; Wang, W.; Liu, X. L.; Fei, W. D.
<x xml:space="preserve">Abstract</x> Upward self-polarization induced by lattice mismatch and defect dipole alignment in (001) BaTiO3/LaNiO3 polycrystalline film at low temperature.